Single-electron transfer radical activations and reactions enabled by carbene organic catalysts and organic reagents - Zhang, Yuexia (2017)
This thesis focuses on exploring new single-electron transfer reaction modes enabled by N- heterocyclic carbene (NHC) organocatalysts and organic reagents. It contains four parts: Chapter 1 gives brief introductions to the development of radical reactions mediated by common radical initiators, photoredox catalysis, transition metal catalysts, electronchemistry and organocatalysts. This chapter also shows the challenges in organocatalyzed single-electron transfer reactions, especially, the limitations in NHC- catalyzed single-electron transfer reactions. Chapter 2 describes a NHC-catalyzed SET process that allows for highly enantioselective entry into β-hydroxyl esters that are widely found in natural products and bioactive molecules. The mechanistic study demonstrates the generation of multiple radical intermediates in this catalytic reaction. Chapter 3 shows an unusual trimerization of enones via a formal [2+2+2] process, which is enabled by NaOtBu and NHC. This study provides a new avenue in using NaOtBu and combined NHC/NaOtBu to generate radical intermediates from enones. Chapter 4 introduces a one-pot approach to synthesis of sulfoxides from alkenes and alkynes, this process is metal-free and no over-oxidatition of sulfoxides to sulfones is observed. N-fluorobenzenesulfonimide (NFSI) is used to enable radical generation for thiol-ene/yne reaction and subsequent selective oxidation of sulfides in situ to sulfoxides.